1992
DOI: 10.1128/aac.36.5.1081
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular activity of zidovudine (3'-azido-3'-deoxythymidine, AZT) against Salmonella typhimurium in the macrophage cell line J774-2

Abstract: The antibacterial effect of zidovudine (AZT) has been demonstrated both in vitro and in vivo with experimental models of gram-negative bacterial infections. It has been associated with the absence or low occurrence of nontyphoid SalmoneUla infections in AIDS patients treated with AZT. Using the macrophage cell line J774-2, we demonstrate the inhibition of intracellular growth of Salmonella typhimurium by AZT. This effect is obtained with one-half of the MIC (1 ,ug/ml) of AZT for S. typhimurium. Inhibition of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…dosing produced an area under the concentration-time curve (AUC) of 0.0014 mg • h/liter and a maximum concentration of drug in serum (C max ) of 0.0015 mg/liter while a 200-mg oral dosing gave rise to an AUC of 0.0017 mg • h/liter and a C max of 0.0018 mg/liter (35). AZT has been shown to be active against Gram-negative bacteria (18)(19)(20), but it is not known if the concentrations used clinically are sufficient to treat bacterial infections in humans. Colistin is effective against multidrug-resistant but colistin-susceptible Pseudomonas aeruginosa, K. pneumoniae, and Acinetobacter (36) strains and importantly against NDM-1-carrying Enterobacteriaceae (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…dosing produced an area under the concentration-time curve (AUC) of 0.0014 mg • h/liter and a maximum concentration of drug in serum (C max ) of 0.0015 mg/liter while a 200-mg oral dosing gave rise to an AUC of 0.0017 mg • h/liter and a C max of 0.0018 mg/liter (35). AZT has been shown to be active against Gram-negative bacteria (18)(19)(20), but it is not known if the concentrations used clinically are sufficient to treat bacterial infections in humans. Colistin is effective against multidrug-resistant but colistin-susceptible Pseudomonas aeruginosa, K. pneumoniae, and Acinetobacter (36) strains and importantly against NDM-1-carrying Enterobacteriaceae (8).…”
Section: Discussionmentioning
confidence: 99%
“…It inhibits viral reverse transcriptase and was the first effective treatment for HIV/AIDS (17) entering the U.S. market in 1986. AZT is also active against Gram-negative bacteria (18)(19)(20)(21)(22) but has not been developed or approved for that purpose. It is thought to inhibit bacterial DNA replication by chain termination.…”
mentioning
confidence: 99%
“…These results suggest that ZDV, which has activity against salmonellae within macrophages (13), may play a role in the suppression of salmonellosis in patients infected with HIV, although microbial resistance can develop. Despite the fact that cross-resistance was not demonstrated, ddC and ddI at currently used dosages would not be expected to have clinical usefulness in the treatment or prevention of Salmonella infections.…”
Section: Discussionmentioning
confidence: 93%
“…Despite adequate antibacterial therapy, frequent relapses have been reported (32). It has been suggested that the recent decrease in frequency of human immunodeficiency virus (HIV)-associated Salmonella bacteremia may be attributable to the widespread use of ZDV (6,13,31). Increasingly, other nucleoside analogs, such as 2',3'-dideoxyinosine (ddI; didanosine) and 2',3'-dideoxycytidine (ddC; zalcitabine), which have undefined anti-Salmonella activity, are being used in the treatment of HIV infection.…”
mentioning
confidence: 99%
See 1 more Smart Citation